PENGARUH PENDIDIKAN KESEHATAN DENGAN METODE GUIDANCE AND COUNSELING TERHADAP PENGETAHUAN WANITA USIA SUBUR UNTUK PENCEGAHAN KANKER SERVIKS - Paramita, Winda Wiranti; Utami, Sri; Hasneli N., Yesi (Coping: Community of Publishing in Nursing, 2023)
Cervical cancer is a malignant disease of the female reproductive organs. One of the interventions that can be done to prevent cervical cancer is to increase the knowledge of women of childbearing age with guidance and counseling methods. The guidance and counseling method can empower clients and develop their potential optimally so as to create awareness for cervical cancer prevention behavior. This study aims to determine the effect of health education about cervical cancer with guidance and counseling methods on the knowledge of women of childbearing age for the prevention of cervical cancer. This study used a pre-experimental design with a one group pre-test post-test design. This study was conducted in the work area of Puskesmas Simpang Baru with a total sample of 55 respondents who were members of one group with purposive sampling technique. The measuring instrument used was a cervical cancer knowledge questionnaire that had been tested for validity and reliability. Data analysis used was univariate and bivariate analysis using Wilcoxon test. The results showed that from demographic data, the majority of respondents were in late adulthood (36-46 years) with a percentage of (49,1%), Minang ethnicity (49,1%), multiparous parity (80%) with a high school / equivalent education level (50,9%) and the majority of respondents' jobs were not working / housewife (72,7%). There was a change in the minimum and maximum values during the pre-test 7-21 which increased during the post-test to 16-22, a change in the mean value during the pre-test and post-test with an increase of 4,13. The results of the Wilcoxon statistical test obtained a p value (0,000) < ? (0,05). This shows that health education about cervical cancer with the guidance and counseling method affects the knowledge of women of childbearing age for the prevention of cervical cancer.